2016
DOI: 10.1097/md.0000000000002584
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Ginseng-Related Therapies in Type 2 Diabetes Mellitus

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 31 publications
1
64
1
1
Order By: Relevance
“…In a study addressing the effect of dosage on the metabolic response to vegetables added to a mixed lunch meal, it was found that the larger the carrot portion, the lower the glucose and insulin/C‐peptide responses and the higher the satiety scores (Gustafsson et al ., ), which may suggest that the large carrot meals could provide sufficient falcarinol to exert this effect. A benefit of ginseng supplementation in improving glucose control and insulin sensitivity in patients with T2DM or impaired glucose intolerance has been concluded from a recent meta‐analysis (Gui et al ., ). Although these data are promising, there is not yet any mechanistic in vivo evidence that this negative dietary mechanism on CB 1 receptor signalling exists.…”
Section: Diet‐induced Shifting Of the Cb1/cb2 Receptor Activation Ratio?mentioning
confidence: 97%
“…In a study addressing the effect of dosage on the metabolic response to vegetables added to a mixed lunch meal, it was found that the larger the carrot portion, the lower the glucose and insulin/C‐peptide responses and the higher the satiety scores (Gustafsson et al ., ), which may suggest that the large carrot meals could provide sufficient falcarinol to exert this effect. A benefit of ginseng supplementation in improving glucose control and insulin sensitivity in patients with T2DM or impaired glucose intolerance has been concluded from a recent meta‐analysis (Gui et al ., ). Although these data are promising, there is not yet any mechanistic in vivo evidence that this negative dietary mechanism on CB 1 receptor signalling exists.…”
Section: Diet‐induced Shifting Of the Cb1/cb2 Receptor Activation Ratio?mentioning
confidence: 97%
“…Much work is needed in this field to establish whether such treatments are not only safe but also efficacious. Two of the most common natural medicines utilized for the prevention and treatment of excess weight and type 2 diabetes are fibres and herbal products such as ginseng …”
Section: Introductionmentioning
confidence: 99%
“…Two of the most common natural medicines utilized for the prevention and treatment of excess weight and type 2 diabetes are fibres and herbal products such as ginseng. [7][8][9][10] Dietary fibres are widely promoted as a useful component of a healthy diet for weight loss and weight control as they increase feelings of satiety after ingestion and add bulk to foods without contributing to energy content, thus displacing other, more energy-dense macronutrients. 9 Fibres also bind dietary fat in the intestine and prevent its absorption; however, the fat-binding capacity of most fibres is small and has a negligible effect on overall energy absorption.…”
mentioning
confidence: 99%
“…improved fasting glucose and post prandial insulin levels were observed when ginseng was 208 administered alone [85].…”
mentioning
confidence: 99%